Words That Work: A Thematic Study of Persuasive Language in Online Advertisements - Harahap, Ahmad Fadli; Losi, Rizky Vita; Elviani, Mutia; Panggabean, Hanna Maria; Hamdanur, Roobby (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
In the rapidly evolving digital era, online advertising has emerged as a central strategy in marketing communication. While language plays a crucial role in crafting persuasive advertisements, few studies have provided a thematic synthesis of the linguistic strategies used in online ads. This study aims to identify and synthesize persuasive linguistic strategies as discussed in recent academic literature. The research employs thematic analysis based on Braun and Clarke’s six-phase framework. Data were collected from ten peer-reviewed journal articles published between 2020 and 2025, each focusing on persuasive language in digital advertising. The analysis revealed four dominant themes: Emotional Resonance, Building Credibility, Interactive Appeal, and Aesthetic Persuasion. These findings demonstrate that language in online advertising is not only used to convey product information but also to establish emotional connections, build trust, stimulate audience engagement, and enhance the aesthetic appeal of the message. The study offers practical implications for advertisers, encouraging a focus on emotional and interactive elements in message construction. It also calls for further research into the effectiveness of these strategies across different digital platforms and cultural contexts.